Use of Ice Cream Containing Probiotic an Effective Way to Control Dental Caries? - Sette-de-Souza, Pedro Henrique (2025)
To perform a systematic review to assess the decrease in bacterial counts of Streptococcus mutans in patients who used ice cream enriched with probiotics. Is registered in the PROSPERO platform, by the code CRD42022371298. The databases were Scopus, Web of Science, Embase, Pubmed, Medline, and Science Direct, through a search algorithm based on the following PICO question: P-individuals systematically healthy and free of caries, I-enriched diet with probiotics, C-diet with ice cream without probiotics, O-S. mutans count after the diet, being only original articles. After the inclusion of metadata in the Rayyan platform, the text were read by two independent researchers, with inter-examiner kappa >0.9, with a final sample of 5 articles. There was a significant reduction of S. mutans, with p-values between <0.001 and <0.005 for all studies analyzed, maintaining the decrease for up to 7 days, conserving it for 90 days after the diet protocol, but in this case without statistical difference. The use of ice cream containing probiotics to reduce the bacterial count of S. mutans is promising, but the ideal strain and the exact number of days for maintenance of the diet are still unknown.